THE INFLUENCE OF MANAGERIAL OWNERSHIP, FINANCIAL DISTRESS, AND EARNINGS MANAGEMENT ON THE INTEGRITY OF FINANCIAL STATEMENTS - Fairuzzaman Fairuzzaman; Prisila Damayanty (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to examine the effects of managerial ownership, financial distress, and earnings management on the integrity of financial reports. The population consists of all property and real estate companies listed on the IDX in 2018-2021. This research used purposive sampling for sampling, which resulted in a total of 10 companies being observed over a 4 year period, collecting a total of 40 research data. Research findings show that managerial ownership and financial distress have a significant and negative influence on the integrity of financial reports. On the other hand, there is no significant influence of earnings management on the integrity of financial statements. Overall, when these factors are evaluated, managerial ownership, financial distress and earnings management simultaneously have an influence on the integrity of financial statements